Representations of women in women's magazines - Ndzamela, Viwe (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2002)
Women's magazines as a popular form of entertainment are among the media products that have been criticised for misrepresenting women. These popular magazines are often condemned for their failure to represent women in a positive light although they claim to target women as their market. The objective of this research is to assess and analyse representations of women in selected women's magazines. Because women's magazines are part of popular culture, which is not only concerned with the production process but also takes into consideration the needs of the readers, the research seeks to find out whether these magazines meet the expectations of its readers. The study is a combination of qualitative analysis, which looks at the frequency and the manner in which women are represented, with a qualitative interpretation of women's roles within those representations. The issue of representations of women in women's magazines is a very complex one as magazines, like other cultural texts are open to multiple interpretations. Consequently, multiple conclusions have been reached and the outcome of the study is therefore a series of three conclusions based on feature articles, advertisements and at a theoretical level.
Keywords: Women in mass media; Women's periodicals, -- South African